Searching for a promising topological Dirac nodal-line semimetal by angle resolved photoemission spectroscopy. (15th December 2021) - Cheng, Zhengwang; Hu, Zhilong; Li, Shaojian; Ma, Xinguo; Liu, Zhifeng; Wang, Mei; He, Jing; Zou, Wei; Li, Fangsen; Mao, Zhiqiang; Pan, Minghu
Abstract: Topological semimetals, in which conduction and valence bands cross each other at either discrete points or along a closed loop with symmetry protected in the momentum space, exhibited great potential in applications of optical devices as well as heterogeneous catalysts or antiferromagnetic spintronics, especially when the crossing points/lines matches Fermi level ( E F ). It is intriguing to find the 'ideal' topological semimetal material, in which has a band structure with Dirac band-crossing located at E F without intersected by other extraneous bands. Here, by using angle resolved photoemission spectroscopy, we investigate the band structure of the so-called 'square-net' topological material ZrGeS. The Brillouin zone (BZ) mapping shows the Fermi surface of ZrGeS is composed by a diamond-shaped nodal line loop at the center of BZ and small electron-like Fermi pockets around X point. The Dirac nodal line band-crossing located right at E F, and shows clearly the linear Dirac band dispersions within a large energy range >1.5 eV below E F, without intersected with other bands. The obtained Fermi velocities and effective masses along Γ–X, Γ–M and M–X high symmetry directions were 4.5–5.9 eV Å and 0–0.50 m e, revealing an anisotropic electronic property. Our results suggest that ZrGeS, as a promising topological nodal line semimetal, could provide a promising platform to investigate the Dirac-fermions related physics and the applications of topological devising.